2004
DOI: 10.1089/088282404322875467
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Strain Differences in the Chemokine Response to Acute Lung Infection with a Murine Gammaherpesvirus

Abstract: Numerous mouse strain-based differences in the immune response and in susceptibility to numerous pathogens have been described, but it is not known if these differences extend to chemokine responses to viral infection of the lungs. To define mouse strain-based differences in the host chemokine response and susceptibility to infection with murine gammaherpesvirus-68 (MHV-68), we compared the induced chemokine response to MHV-68 infection in the lungs of BALB/c and C57BL/6 mice at 1-15 days post-infection. CC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 44 publications
0
35
0
1
Order By: Relevance
“…Pertinent to our study, IFN-g has been shown to prevent EBV-induced B-cell transformation (18), and inhibit HHV-8 production (25), indicating that it likely plays an important role in human gammaherpesvirus infections. Another study reported differences in the immune response between C57BL/6 and BALB/C mice infected with MHV-68, with several differences seen in chemokine production (40). IFN-g was higher in BALB/C mice than C57BL/6 mice, but viral titers were also higher, indicating no correlation with increased resistance to infection (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pertinent to our study, IFN-g has been shown to prevent EBV-induced B-cell transformation (18), and inhibit HHV-8 production (25), indicating that it likely plays an important role in human gammaherpesvirus infections. Another study reported differences in the immune response between C57BL/6 and BALB/C mice infected with MHV-68, with several differences seen in chemokine production (40). IFN-g was higher in BALB/C mice than C57BL/6 mice, but viral titers were also higher, indicating no correlation with increased resistance to infection (40).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported differences in the immune response between C57BL/6 and BALB/C mice infected with MHV-68, with several differences seen in chemokine production (40). IFN-g was higher in BALB/C mice than C57BL/6 mice, but viral titers were also higher, indicating no correlation with increased resistance to infection (40). Also, MHV-68-induced lymphomas in the absence of MHC class I-mediated immune surveillance preferentially occur in the BALB/C background (34).…”
Section: Discussionmentioning
confidence: 99%
“…For the plaque assay, supernatants were aspirated off MEF monolayers and homogenate dilutions were plated in 1 ml complete DMEM. Plates were incubated for 2 h at 37 uC, and the plaque assay procedure was continued as described elsewhere (Weinberg et al, 2004). Titres are expressed as p.f.u.…”
Section: Methodsmentioning
confidence: 99%
“…All DNA extraction procedures were done from homogenized tissue lysates using the QIAamp DNA Mini kit (Qiagen). Real-time quantitative (Q)-PCR was performed using primers and probe against cHV-68 viral DNA as described elsewhere (Weinberg et al, 2004). Mouse bactin primers and probes have been described elsewhere (Schuetze et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Real-time quantitative PCR was performed using primers and probe against gHV-68 viral DNA as previously described (46). Mouse b-actin was used as an internal control with primers and probe as previously described (5).…”
Section: Dna Extraction and Real-time Quantitative Pcrmentioning
confidence: 99%